Penetapan Parameter Mutu Ekstrak yang Memiliki Aktivitas sebagai Antioksidan dari Daun Cincau Hijau (Cyclea barbata L.Miers.) - Erlindha Gangga; Rani Purwati; Yunahara Farida; Kartiningsih Kartiningsih (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
Cincau Hijau leaves (Cyclea barbata L.Miers ) has been used empirically as a medicinal plant because it contains many potential compounds such as flavonoids. Cincau Hijau leaves has been known as antioxidant activity. Determination of pharmacognosy parameters and phytochemical screening of dry leaves and extracts have been carried out as well as determination of total fl avonoids content. Fresh leaves were extracts with water and Dry leaves were macerated with 96% ethanol and were then concentrated by rotavapor to obtain viscous extracts. Free radical scavenging activity of the extracts was evaluated using DPPH method. Afterwards, determination of specifi c and non-specifi c parameters were performed. Results of phytochemical screening of powder and 50% and 96% ethanol extract showed that tall the tested samples contained alkaloid, fl avonoids, saponins, tannins, steroids/ triterpenoids, coumarin. The examination of specifi c parameter showed that the extract has a thick consistency, tawny color, bitter taste, characteristic odor. In addition, water-soluble compound and 96% ethanol extract are 46.64 and 62.13% respectively whereas ethanol-soluble compounds are 39.22 and 74.72%, respectively. While the results of nonspecifi c parameters of 50% and 96 % ethanol extract displayed total ash content of 9.69 and 9.49%, respectively, acid insoluble ash content of 0.30 and 0.16%, respectively, content of water soluble ash of 9.17 and 4.30%, respectively, loss on drying of 9.35 and 8.9%, respectively, water content of 8.45 and 7.25%, respectively. Based on heavy metal contamination, Pb concentration in 50 and 96% ethanol extract are 0.0227 and 0.0333 mg/kg, respectively whereas Cd concentration are 0.1206 and 0.0022 mg/kg, respectively and total number of CFU of 4,22 x 103 and 2,30 x 103 colonies/g, respectively while molds and yeasts number of colony of 0,48 x 102 and 8,88 x 102 colonies/g, respectively. Moreover, the total flavonoid was 0,19 %. Result of DPPH inhibition test showed that IC50 96 % ethanol extract are 83,280 ppm and water extracts are 102,01 ppm